Dynamic experience TRIZ service design model for a case study of expo - Qi, Ye Li (2017)
Customer experience IS a crucial aspect of product or service design. A good customer experience means the great satisfaction of the customer expectation. In the service industry, conversely, the customer experience failure of service performance means the service failure. Service recovery as a measure of service failure handling requires more and more complex failure analysis and customer research. Service failure must spend the massive cost for processing corresponding recovery measures according to a specific failure situation. Attempting to enhance the ability of service recovery and customer experience of Expo (Exposition) process, this research proposes a novel systematic service design approach named "Dynamic Experience TRIZ service design model (DETRIZ model)" that incorporates TRIZ (Inventive Problem Solving Theory), Customer Experience Journey Map (CXJM), service assembly concept and service replace concept. Then, new service systems named smart Expo service were designed for case companies, in order to verify the proposed service design approaches. This dissertation applies the user-centered method, Customer Experience Journey Map. It analyses the customer pain points during the three basic MICE (Meetings, Incentives, Conventions, and Exhibition industries) industries, Exhibition, Tourism, and Hotel. Then, the innovation problem-solving theory (TRIZ) is introduced and utilized to deal with the service provider's pain points. Based on TRIZ innovative principles, the Service Assembly Concept is represented as a resolution to enhancing the customer experience. The service assembly concept cooperating with emotional range analyses, and then design two service assembly mechanisms. The service assembly mechanism improves the overall customer experience. Besides, the service replacement mechanism is a simplest service failure handling measure. A case study of a Kaohsiung exhibition center in Taiwan is taken as the validation. The final empirical result shows the improvements of customer experience satisfaction and effectiveness of failure handling.